Evolving concepts and use of immunohistochemical biomarkers in flat non-neoplastic urothelial lesions: WHO 2016 classification update with diagnostic algorithm. (19th May 2018) - Sanguedolce, Francesca; Brunelli, Matteo; D'amuri, Alessandro; Calò, Beppe; Mancini, Vito; Carrieri, Giuseppe; Cormio, Luigi
Abstract: Context: The classification of flat non-neoplastic urothelial lesions has been evolved through the years in the attempt to better define a spectrum of morphologic entities with somewhat overlapping features. Differentiating these lesions is important because of differences in patient management and clinical outcome. Materials and methods and objective: A systematic review of the literature has been carried out in order to (1) assess the most striking clinical features of each lesion and (2) identify those morphological traits and immunophenotypical markers which may aid in the differential diagnosis. Results and conclusion: Our results point out the importance of a proper definition of flat non-neoplastic urothelial lesions in order to predict clinical behaviour and allow tailored patient management; therefore, we attempted to construct a novel and "easy to use" algorithm for a clear, standardized and evidence-based pathological diagnosis.